The effect OF Cr, Cr-N and Cr-Ox coatings on deuterium retention and penetration in zirconium alloy Zr-1Nb - Kopanetz, I.E.; Tolstolutskaya, G.D.; Nikitin, A.V.; Bilous, V.A.; Kuprin, A.S.; Ovcharenko, V.D.; Vasilenko, R.L. (Вопросы атомной науки и техники, 2015)
Depth distribution profiles of deuterium in zirconium alloy Zr-1Nb in initial state and with coatings Cr, CrN, and Cr₂O₃ after ion implantation with 15 keV/D⁺ at temperatures 350 °C to dose 1·10¹⁷ D/cm⁻² and deuterium plasma of glow discharge at room temperature are determined by the method of nuclear reactions. It is shown that in studied range of temperatures and concentrations of deuterium coatings CrN and Cr₂O₃ act as barrier and protect zirconium from interaction with hydrogen isotope.